2022
DOI: 10.1186/s43168-021-00109-3
|View full text |Cite
|
Sign up to set email alerts
|

To what extent AstraZeneca ChAdOx1 nCoV-19 vaccine is safe and effective? Rapid systematic review

Abstract: Until now, there are more than two hundred million confirmed cases of COVID-19 including more than seven million deaths. Clinical trials of all three vaccines authorized for use in the UK (Pfizer–BioNTech, Oxford–AstraZeneca, and Moderna) have reported high vaccine efficacy. This rapid systematic review was initiated because no systematic review had been conducted to determine the safety and efficacy of AstraZeneca ChAdOx1 nCoV-19 vaccine. Evidence acquisition: A systematic search in the following platforms: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Epidemiological studies on vaccine effectiveness had been carried out in various countries as it is necessary to complement the results of pre-licensing trials to estimate the efficacy of these vaccines at the population level in real-world conditions and had offered best practice guidance on how to undertake post-introduction evaluations of the effectiveness of COVID-19 vaccines. [ 7 8 ] Observational studies conducted in different countries indicated the high effectiveness of the vaccine in preventing severe outcomes. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies on vaccine effectiveness had been carried out in various countries as it is necessary to complement the results of pre-licensing trials to estimate the efficacy of these vaccines at the population level in real-world conditions and had offered best practice guidance on how to undertake post-introduction evaluations of the effectiveness of COVID-19 vaccines. [ 7 8 ] Observational studies conducted in different countries indicated the high effectiveness of the vaccine in preventing severe outcomes. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Another vaccine study from Chile found that, among persons who were fully immunized with CoronaVac, the adjusted vaccine effectiveness was 65.9% (95% confidence interval [CI], 65.2 to 66.6) for the prevention of COVID-19 and 87.5% (95% CI, 86.7 to 88.2) for the prevention of hospitalization, 90.3% (95% CI, 89.1 to 91.4) for the prevention of intensive care unit (ICU) admission, and 86.3% (95% CI, 84.5 to 87.9) for the prevention of COVID-19-related death. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%